The impact of corporate governance and capital structure on firm performance and firm value: Evidence from Shariah-compliant fir - Nikmah, Choirul; Hung, Rern-Jay (Technium Social Sciences Journal, 2025)
Corporate governance is an important factor in generating firm financial performance especially in the Covid-19 Pandemic. During the pandemic, the government announced to do social distance that effect on firm operation which could not run maximal comparing to normal conditions. Good corporate governance practice may help to prevent deterioration financial ratio due to decreasing firm financial performance. Moreover, external funding becomes important to back up back up firm operations because firm tend to suffering loss during the pandemic. The aims of this study are to analyse the impact of corporate governance practice and capital structure on firm performance, as well as firm value. This study applies Shariah-compliant firms (SCF) that listed on Indonesia stock exchange from 2015 – 2020. This study analyses using structural equation modelling - partial lease square (SEM-PLS). The results show that corporate governance have a significant positively on firm financial performance, but capital structure shows the adverse effect on firm financial performance. In terms of firm value, both corporate governance and firm financial performance have a positively associated to firm value. Moreover, firm financial performance has negatively impact on firm value. Finally, the findings may help stakeholders to create effective corporate governance practice in driving both firm performance and firm performance, as well as maintain the balance between debt and equity to optimize capital structure that may impact on the firm financial performance and firm value.